Syair Perahu Hamzah Fansuri (Analisis Pendidikan Akhlak) - Wahidin, La Ode; Gadafi, Muamal; Hasan, Hasni; Husriadi, Muh. (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
The main question of this research is what is the content of moral education in the poem Perahu by Hamzah Fansuri. The aim of the research is to determine the content of moral education in the poem Perahu by Hamzah Fansuri. The benefit of this research is that it attempts to straighten out negative accusations against Hamzah Fansuri and to develop knowledge of Islamic education. The sample was taken from the poem Perahu Hamzah Fansuri. In collecting data, the author took the following steps: first, studying the content of the Perahu poetry which is related to the moral content relevant to the research topic, second, studying several writings related to the poetry as a secondary source. The results of the study of akhlaq education are: First, in stanzas 1 to 12, an explanation of akhlaq towards fellow humans. Second, in stanzas 13 to 26, the explanation of ahklaq to Allah Almighty because it reminds the reader to follow Allah Almighty. Third, in stanzas 27 to 32 the moral explanation of fellow human beings. Fourth, stanzas 33 to 38, Hamzah fansuri explains the akhlaq of the Prophet Muhammad (peace be upon him). Fifth, in stanzas 39 to 42, an explanation of akhlaq towards Allah (swt) because in the poem it reminds the reader of the sentence tawhid.